Association of single nucleotide polymorphisms of MTHFR, TCN2, RNF213 with susceptibility to hypertension and blood pressure. Issue 12 (17th December 2019) - Liu, Shan; Liu, Mengwei; Li, Qian; Liu, Xiuping; Wang, Yue; Mambiya, Michael; Zhang, Kaili; Yang, Luping; Zhang, Qian; Shang, Mengke; Zeng, Fanxin; Nie, Fangfang; et al.
Abstract: Methylenetetrahydrofolate reductase gene ( MTHFR ), transcobalamin II ( TCN2 ) and ring finger protein 213 ( RNF213 ) are related to homocysteine (Hcy) level and are of great significance for hypertension. We aimed to evaluate the associations of MTHFR (rs1801133, rs1801131, rs9651118), TCN2 (rs117353193) and RNF213 (rs9916351) with hypertension and blood pressure (BP). A total of 953 patients with hypertension and 1103 controls were enrolled. Genotyping was performed by Taqman. Logistic regression analysis indicated that A allele of TCN2 rs117353193 under the dominant model had a significantly protective effect ( P =0.045) after adjustment, which showed that AA+GA genotype has a lower risk than GG. Additionally, the average diastolic BP (DBP) ( P =0.044) and mean arterial pressure (MAP) ( P =0.035) levels were significantly different between genotypes of RNF213 rs9916351. Further pairwise comparison showed that the average systolic BP (SBP) level of the TT genotype carriers were significantly higher than in CC ( P =0.024), and the average DBP and MAP levels of the TT genotype carriers were higher than in CT ( P =0.044, P =0.012, respectively) and CC ( P =0.048, P =0.010, respectively). In the recessive model, the average SBP ( P =0.043), DBP ( P =0.018) and MAP ( P =0.017) levels with the TT genotype carriers were significantly higher than in CT+CC. Multiple linear regression analysis suggested that RNF213 rs9916351 in the recessive model had significant effects on SBP ( P =0.025), DBP ( P =0.017) and MAP ( P =0.010) as a risk factor. However, no associations were observed between MTHFR and hypertension. TCN2 rs117353193 might serve as a protective factor in hypertension, and RNF213 rs9916351 might be a risk factor that is linked to increase BP level in Northeast Chinese population.